Золотоординські кочівники за матеріалами некрополя біля села Волошине - Долженко, Ю.В. (Археологія, 2019)
Спираючись на дані етнічної краніоскопії було опрацьовано 46 черепів з поховань Золотоординського часу, які дослідив О.Б. Супруненко поблизу с. Волошине Полтавської обл. За більшістю ознак ця серія належить до південних європеоїдів, однак окремі показники дають підставу припустити східну антропологічну домішку. Памятники золотоордынского времени за последние годы стали хорошо известны в степных районах Полтавщины — в низовьях Сулы, Псла, Сухого Кобелячка, Ворсклы и Орели. Днепровские, Пселская и Ворсклинская переправы, действовавшие в эпоху развитого и в начале позднего средневековья, обусловили появление здесь стойбищ кочевников, обеспечивавших функционирование и охрану дорог и переправ, возможно, также работу таможен на берегах Днепра. В июле—сентябре 2003 и в 2005 г. Охранная археологическая экспедиция Центра охраны и исследований памятников археологии управления культуры Полтавской облгосадминистрации исследовала курганы и курганные насыпи между сс. Дуканичи, Волошино и Солонцы Полтавской обл. Антропологический материал включает 46 скелетов. После обработки 46 черепов и их фрагментов (23 мужских и 22 женских, 1 — неопределенного пола) установлено, что частота подорбитного узора типа II (ПОВ-II) на черепах из Волошино низкая. Это указывает на принадлежность группы к южным европеоидам. Показатели клиновидного верхнечелюстного шва (КВШ) оказались умеренными. Затылочный индекс (ЗИ) из исследуемого могильника по процентной доле повышен (восточное направление связи); Задневисочный шов (ЗВШ) на черепах исследуемой группы отсутствует, что указывает на ее европеоидность. По данным умеренного индекса поперечно-небного шва (ИПНШ) можно считать исследуемую серию пребывающей на стыке между европеоидными и монголоидными показателями по данному признаку, но тяготеющую к европеоидным популяциям. Проценты надорбитных отверстий (НО) на черепах повышены, что указывает на восточный вектор связей этой группы людей. По данным многомерного анализа главных компонент выявлено, что исследуемая серия черепов из Волошино ХІІІ—ХІV вв. больше тяготеет к половецкой группы ХІ—ХІІІ вв. из Донецкой обл. и населению Нижнего Поднепровья (Мамай Сурка ХІІ—ХV вв.). Monuments of the Golden Horde history had become well-known recently in Poltava region, especially in its steppe districts (in the lower basins of the Sula, Psel, Suhy Kobeliachok, Vorskla and Oril rivers). The crossings on Dnieper, Psel and Vorskla functioning in developed Medieval Period and at the beginning of the Late Medieval Period have caused emergence of nomads’ camps. The camps maintained and protected roads and crossings as well as, probably, sustained customs on the banks of the Dnieper, nearsubmerged Perevolochna, Keleberda and Kremenchuk. The Protective archaeological expedition of Centre for the Protection and Investigation of Archaeological Sites (Cultural Department of Poltava Regional State Administration) have explored the grave mounds of the Group 2 on a piece of land intended for ferruginous quartzite quarry of the company “Ferrexpo Yeristovo Mining” in July - September 2003 and in summer 2005. Theworks were carried out 7,0- 7,2 km to the north and north-east of Horishni Plavni (former Komsomolsk) between the villages of Dukanychi, Voloshyne and Solontsi (Dmytriv village council of Horishni Plavni municipality, Poltava region). As a result, anthropological material has been given to the author’s study. After studying of 46 skulls and their parts (period of the Golden Horde, Voloshyne area) it was found out, that the frequency of the 2nd type of underorbital patterns on the skulls from Voloshyne is low. It is a feature of the Southern Caucasians. The indexes of sphenomaxillary suture are moderate. Occipital index from the grave field under investigation is increased according to the percentage (eastern vector of connections). Posterior zygomatic suture on the skulls of probed group is absent. It is typical for the Caucasians. Index of transverse palatine suture is moderate and indicates the series as a border-line between Caucasians and Mongoloids according to the mentioned feature and closer to European populations. The percentage of supraorbital foramens on the skulls is increased (eastern vector of connections). Multivariate principal component analysis has shown that the explored series is closer not to the groups of the interfluve of the Volga and Ural, Kurai valley or Transbaikal, but to people from the Lover Dnieper basin (Mamay Surka) according to ethnical cranioskopy, when male and female skulls are considered together.